Pyridinium-fused pyridinone : a novel “turn-on” fluorescent chemodosimeter for cyanide - Li, Junbo (2014)
A new chemodosimeter based on pyridinium-fused pyridinone iodide (PI) has been obtained through a “clean reaction” method. This compound can detect CN− in aqueous solution with a high selectivity and rapid response. The detection of CN− occurs through the nucleophilic attack of CN− on the C[DOUBLE BOND]N bond, which induces the destruction of the π-conjugation on the pyridinium ring. Support of this detection mechanism was obtained by 1H NMR titration, HR-MS, and DFT calculations. Upon the addition of 10 equivalents CN− to a solution of PI in THF/H2O (1:1, v/v), a 57-fold enhancement in fluorescence intensity was observed at the maximum emission wavelength of 457 nm. Meanwhile, the maximum absorption wavelength was also blue-shifted from 447 nm to 355 nm. Other common anions such as BF4−, PF6−, F−, Cl−, Br−, I−, H2PO4−, ClO4−, CH3COO−, NO2−, N3−, and SCN− had little effect on the detection of CN−. The response time of PI for CN− was less than 5 seconds. The detection limit was calculated to be 5.4×10−8 m, which is lower than the maximum permission concentration in drinking water (1.9 μm) set by the World Health Organization (WHO).